2020
DOI: 10.3389/fonc.2020.00817
|View full text |Cite
|
Sign up to set email alerts
|

Nimotuzumab for Patients With Inoperable Cancer of the Head and Neck

Abstract: EGFR activation induces cell proliferation, neoformation of blood vessels, survival, and metastasis of the cancer cells. Nimotuzumab is an engineered, intermediate affinity anti-EGFR antibody, that apart from other drugs in its class, is very safe and does not cause hypomagnesemia or grade 3-4 cutaneous rash. The antibody inhibits cell proliferation and angiogenesis, activates natural killer cells, stimulates dendritic cell maturation, and induces cytotoxic T cells. Nimotuzumab restores MHC-I expression on tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…Nimotuzumab was very safe, and only two patients had tremors, chills or headache. Adverse reactions commonly seen in cancer trials consist mostly of fatigue, nausea, vomiting, chills, anorexia and fever [ 16 , 20 , 35 ]. Other recently recommended anti-inflammatory drugs for COVID-19, like tocilizumab or baricitinib, might provoke serious adverse reactions including bacteremia and lung abscess [ 36 ] or grade 3 or 4 adverse events such as hyperglycemia, anemia, decreased lymphocyte count and acute kidney injury, respectively [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nimotuzumab was very safe, and only two patients had tremors, chills or headache. Adverse reactions commonly seen in cancer trials consist mostly of fatigue, nausea, vomiting, chills, anorexia and fever [ 16 , 20 , 35 ]. Other recently recommended anti-inflammatory drugs for COVID-19, like tocilizumab or baricitinib, might provoke serious adverse reactions including bacteremia and lung abscess [ 36 ] or grade 3 or 4 adverse events such as hyperglycemia, anemia, decreased lymphocyte count and acute kidney injury, respectively [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nimotuzumab efficacy results have been reported in more than 40 clinical trials, conducted primarily in patients with advanced cancer, including glioblastoma, squamous cell carcinoma of the head and neck, and esophageal, nasopharyngeal, pancreatic and non-small-cell lung cancers [ 14 , 16–21 ].…”
mentioning
confidence: 99%
“…In general, nimotuzumab is a very safe drug because it has an intermediate affinity against EGFR which facilitates preferential uptake by tissues with high EGFR expression [ 27 ]. Most frequent nimotuzumab-related events in cancer comprise mild or moderate anorexia, chills, headache, fatigue and fever; nimotuzumab does not induce skin rash or hypomagnesemia like other EGFR-targeting drugs [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical studies have shown that the antitumor response evoked by nimotuzumab is mediated by antiproliferative, antiangiogenic and proapoptotic mechanisms [ 27 , 28 ]. Clinical trials have demonstrated that the antibody, in combination with radiation and chemotherapy, significantly increases the survival and objective response rate of patients with advanced epithelial tumors [ 29–35 ].…”
mentioning
confidence: 99%
“…Nimotuzumab is an intermediate affinity anti-EGFR antibody that inhibits cell proliferation and angiogenesis, activates natural killer cells, stimulates dendritic cell maturation, induces cytotoxic T cells, and restores MHC-I expression on tumor cells, hindering one of the EGFR immune-escape ways. In patients with locally advanced SCC of the head and neck, nimotuzumab in combination with low-dose cisplatin and radiotherapy was superior to cisplatin and radiotherapy in progression-free survival, disease-free survival, and locoregional tumor control ( 42 ). Triprilimab (JS001) is a recombinant humanized IgG4 anti-PD-1antibody that has demonstrated clinical activity in heavily pretreated nasopharyngeal cancer ( 43 ).…”
Section: Immune Therapymentioning
confidence: 99%